Integrating Decision Support Systems in Education: A Comprehensive Approach - Pendais Hak; Kundharu Saddhono; Putri Hana Pebriana (STAI Hubbulwathan Duri, 2023)
The current study examined educational Decision Support Systems (DSS) using the Simple Additive Weighting (SAW) method. This study evaluated traditional face-to-face teaching, online learning, and blended learning based on four criteria: effectiveness, cost efficiency, accessibility, and technological requirements. Each criterion was weighted according to its importance. After standardizing and weighting the selection matrix, each instructional style was given a composite score for direct comparison. Blended learning outperformed the other methods, scoring 0.620. The findings suggest that integrating digital and traditional education could boost efficiency. However, the model was sensitive to weighting assignments and couldn't account for nuanced qualitative factors. Refined weight assignment, qualitative variables, and AI could improve schooling and other decision-making in the future. This study showed that DSS and SAW can help make educated education decisions.